1996
DOI: 10.1113/jphysiol.1996.sp021678
|View full text |Cite
|
Sign up to set email alerts
|

Salbutamol changes the molecular and mechanical properties of canine skeletal muscle.

Abstract: 1. Salbutamol, a fl2-agonist, increased the weight of the canine latissimus dorsi muscle. It also increased fusion frequency, and decreased time-to-peak tension, half-relaxation time, and total contraction time. These changes in twitch times and fusion frequency were associated with changes in the levels of proteins expressed in slow-and fast-twitch fibres. Salbutamol decreased the levels of the slow-twitch cardiac isoform of sarco-/endoplasmic reticulum Ca2P-ATPase (SERCA2a) and phospholamban proteins, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
33
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 37 publications
5
33
0
Order By: Relevance
“…Our finding of three MHC isoforms is consistent with the results of Zhang et al [1996] who demonstrated three isoforms with SDS-polyacrylamide gel electrophoresis in the vastus intermedius and latissimus dorsi muscles of dogs. Though fibres only expressing the MHCIIx isoform were not found during the present study, this isoform might be more abundantly expressed in other canine muscles, especially in those involved in more phasic contractions.…”
Section: Discussionsupporting
confidence: 82%
“…Our finding of three MHC isoforms is consistent with the results of Zhang et al [1996] who demonstrated three isoforms with SDS-polyacrylamide gel electrophoresis in the vastus intermedius and latissimus dorsi muscles of dogs. Though fibres only expressing the MHCIIx isoform were not found during the present study, this isoform might be more abundantly expressed in other canine muscles, especially in those involved in more phasic contractions.…”
Section: Discussionsupporting
confidence: 82%
“…MHC-I, -IIa and -IIx, are expressed in canine skeletal muscles [Štrbenc et al, 2004]. In the present study, using SDS-PAGE combined with the immunoblotting technique, we confi rmed our previous fi ndings and the assumptions that only two fast MHC isoforms are expressed in large canine skeletal muscles and that they correspond to MHC-IIa and -IIx of rats [Amann and Fraga, 1992;Amann et al, 1993;Zhang et al, 1996]. To our knowledge, this is the fi rst study of canine skeletal muscles in which electrophoretic MHC isoform bands were identifi ed by the immunoblotting technique.…”
Section: Discussionsupporting
confidence: 78%
“…It has been shown previously that treatment with the ␤ 2 -agonist salbutamol for 6 wk increased SERCA1 protein levels in canine latissimus dorsi and vastus intermedius muscles (36). Similarly, our findings show that fenoterol treatment increased SERCA1 protein levels in the RG and WG muscle of both adult and aged rats.…”
Section: Discussionsupporting
confidence: 74%
“…However, the mechanisms responsible for this change in contractility have not been elucidated. It has been demonstrated that a 6-wk administration of the ␤ 2 -agonist salbutamol can reduce contraction time in canine skeletal muscle (36). Salbutamol treatment also increased the rate of SR Ca 2ϩ resequestration, which suggested that changes in skeletal muscle contractile parameters were mediated by alterations in SR proteins, namely a ␤ 2 -agonist-mediated induction of SERCA1 protein levels (36).…”
mentioning
confidence: 99%
See 1 more Smart Citation